p, and I have Absolutely No Justification for Believing that p: The Incoherence of Bayesianism - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2005)
Bayesianism tells a story about the epistemic trajectory of an ideally rational agent. The agent begins with a ‘prior’ probability function; thereafter, it conditionalizes on its evidence as it comes in. Consider, then, such an agent at the very beginning of its trajectory. It is ideally rational, but completely ignorant of which world is actual. Let us call this agent ‘superbaby’.1 We show that superbaby is committed to sincerely asserting propositions of the form [p and I am not justified in believing that p].